Application of the Agropolitan Concept through Digital Marketing Training and Environmental Implications for MSMEs in Gunung Anyar District, Surabaya City - Harya, Gyska Indah; Mindari, Wanti; Setyadi, Taufik; Pratama, Arista; Mukaromah, Siti; Fadil, Cholid (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Gunung Anyar District in Surabaya focuses on agropolitan development to encourage regional economic growth, especially in agribusiness. Micro, Small, and Medium Enterprises (MSMEs) are important in improving the economy, reducing unemployment, and improving welfare. However, MSMEs face challenges with branding, digital marketing, and environmental impact. The community service program by UPN Veteran East Java aims to support the development of MSMEs through digitalization, product branding, and product diversification. The program also discusses environmental issues, including waste management and Urban Farming. Collaboration between local governments, MSMEs, and the community is essential for the success of this program. The program aims to overcome barriers such as low sales turnover and limited market access, strengthen the position of MSMEs in a competitive market, and become an example of sustainable business practices. The Lecturer Team conducts continuous socialization and assistance related to MSME skills in implementing digital marketing, training and mentoring